2010
DOI: 10.1111/j.1743-6109.2010.01875.x
|View full text |Cite
|
Sign up to set email alerts
|

Injections of Adipose Tissue-Derived Stem Cells and Stem Cell Lysate Improve Recovery of Erectile Function in a Rat Model of Cavernous Nerve Injury

Abstract: Introduction Erectile dysfunction (ED) remains a major complication after radical prostatectomy. The use of adipose tissue-derived stem cells (ADSC) has shown promising results for the treatment of ED. However, the mechanisms of action for stem cell therapy remain controversial, with increasing evidence pointing to paracrine pathways. Aim To determine the effects and to identify the mechanism of action of ADSC and ADSC-derived lysate in a rat model of cavernous nerve (CN) crush injury. Methods Thirty-two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
236
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 240 publications
(252 citation statements)
references
References 41 publications
11
236
2
3
Order By: Relevance
“…Some studies confirmed that embryonic stem cells can be used for the treatment of neurogenic ED (Eglitis and Mezey 1997). Studies of the effect of mesenchymal (Bivalacqua et al 2007;Qiu et al 2012), human neural crest (Song et al 2008), and adipose tissue-derived stem cells (Albersen et al 2010;Garcia et al 2010;Huang et al 2010) on ED treatment have also been performed by other researchers using intracavernous injection of these cells in rats. The results indicated that ED could be improved to a certain extent when treated with these cells.…”
Section: Introductionmentioning
confidence: 95%
“…Some studies confirmed that embryonic stem cells can be used for the treatment of neurogenic ED (Eglitis and Mezey 1997). Studies of the effect of mesenchymal (Bivalacqua et al 2007;Qiu et al 2012), human neural crest (Song et al 2008), and adipose tissue-derived stem cells (Albersen et al 2010;Garcia et al 2010;Huang et al 2010) on ED treatment have also been performed by other researchers using intracavernous injection of these cells in rats. The results indicated that ED could be improved to a certain extent when treated with these cells.…”
Section: Introductionmentioning
confidence: 95%
“…Similar tests conducted by Das et al [88] and Ryu et al [89] in models of diabetic ED additionally found improved erectile function and recovery of pathological changes in SVF treated groups. Our previous work also illustrated the beneficial effect of immediate and delayed intracavernous injection of uncultured autologous SVF, penile injection of ADSCs or ADSC derived lysate in CNI model [90,91]. We also proved the beneficial effect of ADSCs on radiation induced ED model, hyperlipidemia induced ED model, and type 2 diabetes induced ED model [92][93][94].…”
Section: Erectile Dysfunction (Ed)mentioning
confidence: 54%
“…126 Third, ADSCs and cell-free lysates derived from ADSCs were injected into the penis in a rat model of cavernous nerve injury, resulting in a significant recovery of erectile function in both treatments compared with the control group. 127 In the treated rats, nNOS and smooth muscle content were preserved, and less fibrosis occurred in the corpus cavernosum. The underlying mechanisms involved neuron preservation and cytoprotection by inhibition of apoptosis by releasing intracellular preformed substances or by active secretion of certain biomolecules.…”
Section: Adscsmentioning
confidence: 90%